Impact of Genetic Targets on Cancer Therapy - El-Deiry, Wafik S. (Springer New York : Imprint: Springer, 2013)
The volume provides a forum for original peer-reviewed short communications, full-length research and review articles on new research findings and developments on the topic of genetic targets on cancer therapies. As the field is highly important it requires co-operation between research communities from all over the world to share their knowledge and experience in order to move the field forward. Each chapter includes a discussion of the impact of the tumor microenvironment and cancer stem cells and cover current knowledge in this area as it pertains to the disease, including emerging therapy targeting the microenvironment and/or cancer stem cells.